Major factors affecting Foreign Exchange rates - Yelesh, Arman (M. Narikbayev KAZGUU University, 2017)
This research held for revealing changes in exchange rates as one of the usual daily event. Nowadays this changes significantly affect to the entire Kazakhstan economy. We have understood which factors are directly affecting to the exchange rate. The main goal of this research was the analysis of the current situation on the market based on the historical data basis. For achievement of our purpose, we have determined certain steps as follow: searching for specialized literature and researches with different approaches, which was used in our research; developing the data base as main part of this research based on statistical data and samples; running regression models using specific software for macroeconomic analysis; elaborating certain strategies and recommendations. During the research we have determined certain factors such as current account balance, gross domestic product (GDP), consumer price index (CPI) which are influenced to the exchange rate immediately. Also we have considered devaluation processes and currency interventions on the market. This research allows to examine how the whole system works and how to make forecasts for the future periods through computer modeling.
Keywords: Foreign Exchange rates, economy of Kazakhstan, currency interventions